Psychological Empowerment and Improved Professional Performance as a Result of Effective Information Management - Pinto, Cláudia; Carvalho, Milena; Martins, Susana (Bobcatsss, 2023)
Information is essential for organizations. Information and knowledge, associated with technological and scientific advances are, nowadays, easily accessible to all organizations, so whoever holds more information and knows how to manage it in the most adequate way to their vision and style, will be able to acquire a competitive advantage faster than the competitors. In a highly competitive environment for companies today, managers must realize the need to design strategies for organizations based on information as a valuable asset. Companies structure and classify information based on their structure, functions and activities, that is, based on documentary production, information flows between departments, safeguarding and proving what this information constitutes. At Goweb Agency, Lda., the target company of this study, except for the document templates that were intended for commercial proposals and directly linked to sales, most documents existed only for the purpose of quality certification. All documents were organized validly, intuitively and based on the information needs of employees. However these documents weren’t used or even known by the employees. The project planning and the accountability for everyday tasks were lacking meaning to them and conflicts were a constant. By incorporating the documents that described the responsibilities and assignments of each function into the routine tasks of everyday life and encouraging their use, creating and adapting the sharing and management of information in the company's activities, there has been a reduction in internal conflicts among employees, an increase in their degree of satisfaction and motivation, its efficiency and effectiveness and the satisfaction of the company's customers, due to the performance and quality of the work presented. In order to maintain each employee’s accountability and therefore their motivation in doing a better work it is important to continue to invest in the management of information appropriate to the business area of the company, make known the existence of essential information to each workplace and make the access to documentation quick and intuitive for all employees.